2014
DOI: 10.1007/s13659-014-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking of Bacosides with Tryptophan Hydroxylase: A Model to Understand the Bacosides Mechanism

Abstract: Tryptophan hydroxylase (TPH) catalyses l-tryptophan into 5-hydroxy-l-tryptophan, which is the first and rate-limiting step of serotonin (5-HT) biosynthesis. Earlier, we found that TPH2 up-regulated in the hippocampus of postnatal rats after the oral treatment of Bacopa monniera leaf extract containing the active compound bacosides. However, the knowledge about the interactions between bacosides with TPH is limited. In this study, we take advantage of in silico approach to understand the interaction of bacoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As per recent evidence, Bacopa monnieri alcoholic extract has been reported to possesses neuroprotective action by reversing the memory impairment due to pilocarpine treatment in rats by up regulating the expression of the NMDA glutamate receptor GluN1 subunit in the hippocampus [ 75 ] and activity of the NMDA receptor in the cerebral cortex [ 76 ]. Also, it is likely that the CDRI-08modulates various neurotransmitters such as acetylcholine (ACh), serotonin, GABA, glutamate and dopamine in different brain regions that play role in enhancement of the cognitive functions [ 37 , 77 ]. A similar report has been published on effects of the curcumin, a known antioxidant, on the recovery of memory loss in rats by lowering the excitotoxicity by modulating the role of AMPA and NMDA glutamate receptors and thereby the synaptic plasticity in STZ-induced diabetic rats [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per recent evidence, Bacopa monnieri alcoholic extract has been reported to possesses neuroprotective action by reversing the memory impairment due to pilocarpine treatment in rats by up regulating the expression of the NMDA glutamate receptor GluN1 subunit in the hippocampus [ 75 ] and activity of the NMDA receptor in the cerebral cortex [ 76 ]. Also, it is likely that the CDRI-08modulates various neurotransmitters such as acetylcholine (ACh), serotonin, GABA, glutamate and dopamine in different brain regions that play role in enhancement of the cognitive functions [ 37 , 77 ]. A similar report has been published on effects of the curcumin, a known antioxidant, on the recovery of memory loss in rats by lowering the excitotoxicity by modulating the role of AMPA and NMDA glutamate receptors and thereby the synaptic plasticity in STZ-induced diabetic rats [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include Bacosides A1–A3, Bacosides I–III and Bacosaponins A–G [ 36 ]. Recent studies have linked nootropic and neuroprotective role of Bacopa extract with its two major saponins- Bacosides A and B [ 29 , 37 ]. Ethanomedicine researchers have been keenly looking for the precise molecular mechanism underlying the action of its extract in recovery of the cognitive loss due to DM.…”
Section: Introductionmentioning
confidence: 99%
“…This could be one of the mechanisms that enhance the learning and memory processing and it fits well into established concept in different models [ 66 , 67 ]. In addition to these studies, in silico analysis suggested that interaction of bacosides (A, A 3 ) with TPH2 possibly alters the activity of TPH2 that could be one of the mechanisms for increased 5-HT synthesis [ 68 ].…”
Section: Bme Treatment Regulates the Synthesis Of Serotoninmentioning
confidence: 99%
“…The observed lowering could be due to the downregulation of nAChR by BA. Apart from its ability to induce downregulation of nAChR expression, BA could have interacted with tyrosine hydroxylase [ 112 ] and modulated the release of catecholamines.…”
Section: Resultsmentioning
confidence: 99%